The use of sonication treatment to completely decellularize aorta tissue - Noor Azmi, Azran Azhim; Yamagami, K.; Muramatsu, K.; Morimoto, Y.; Furukawa, K. S.; Tanaka, M.; Fukui, Y.; Ushida, T. (Springer, 2013)
We have developed a novel sonication decellularization system to prepare completely decellularized bioscaffolds in a short treatment time. The aim of the study is to investigate the sonication decellularization efficiency and its relation with ultrasonic power output and dissolved oxygen (DO) concentration in different detergent solution. In the study, we used aorta samples to evaluate sonication decellularization efficiency, which assessed treatment duration, washing treatment after decellularization, SDS detergent with/without saline. The treated samples were evaluated histologically by Hematoxylin Eosin (HE) and diamidino-2-phenylindol (DAPI) stains. The concentration of DO was monitored to identify the effect of sonication on cavitation-related DO concentration in the solution. From histological results, the sonication decellularization efficiency was better than the other preparation methods. There were less than 2.0% of DNA remains after sonication decellularization treatment. Decellularization efficiency increased significantly which treated by sonication in SDS without saline as its DO value smaller compared with treatment in SDS with that. In conclusion, we conclude that sonication treatment is capable to use for preparation of the complete decellularized scaffolds in short treatment time